The boomerang of desires in the epoch of immediate satisfaction - Ciaramelli, Fabio (Acta Bioethica, 2001)
In fighting against the risk of the globalization of hazardous food production it is essential to think about psico-sociocultural dimensions of consumerism, whose premises rest on the imperative of immediate satisfaction of desires. Departing from the thesis that multiplication of desires along with their complete and immediate fulfillment unavoidably provoke the overestimating of them, the paper analyzes the «mad cow syndrome» as the tip of the iceberg in the context of our relation with food consumption. In this sense, the matter of collective safety does not imply solely the searching for effective solutions against probable food contagion, but eminently to shed light over the dangerous consequences of a way of living in which everything is reduced to consumption.